ASSESSMENT OF BIOFUEL PRODUCTION TECHNOLOGIES FROM MICROALGAE AND ORGANIC WASTE - Pavliukh , Lesia; Lialuk, Natalia; Horbachova, Olena (Science-based technologies, 2022)
Today, the processing of organic matter, such as organic waste or microalgae, is an important way to renewable energy sources. To maintain a prosperous life of the population, it is critical that renewable sources of energy be found. Problem statement. In the near future, mineral and organic reserves of the earth’s interior will cease to meet the growing energy needs of civilization. Already today, technologies have emerged that allow the production of fossil fuels based on many plant species. But the cultivation of such crops leads to depletion of land resources. In other words, the top and thin fertile layer of humus is gradually depleted, which can lead to the use of millions or billions of hectares of arable land. And here to replace usual terrestrial cultures come microalgae. Research methodology. The study was based on the analysis of theoretical studies and comparison of different types of biological fuels from plant-type and microalgae, at the economic, environmental and social levels. Results and discussion. Biodiesel from microalgae is a third generation fuel obtained by processing vegetable raw materials. It is known that algae are characterized by a high content of fatty acids, which are the basis for the production of biodiesel. Microalgae are very cheap and, at the same time - highly productive raw materials. One hectare of microalgae produces 30 times more biofuel than one hectare of soybeans. At the same time, biofuel from algae is 5-10% more energy-intensive than biodiesel from vegetable oils. In addition, microalgae grow quite rapidly. For example, algae, which is 80% composed of substances similar in origin to oil, grows in 10 days, while the same algae, which is 30% composed of substances similar in origin to oil, grows in only 3 days. Another advantage of using algae is the fact that, unlike growing other types of plant materials, they do not need to be fed and fertilized - they use carbon dioxide (CO2) for growth. The higher the concentration of carbon dioxide, the faster they are cultivated. Thus, the cultivation of microalgae can solve several problems: the problem of the greenhouse effect; the problem of employment of sown areas; the problem of shortages of traditional fuels and many other equally important problems. Conclusion. Organic susstance as microalgae have been experimented as a potential feedstock for biofuel generation in current era owing to its’ rich energy content, inflated growth rate, inexpensive culture approaches, the notable capacity of CO2 fixation, and O2 addition to the environment. The implementation of the technology of biofuel production from organic waste also warns of danger, first of all for people. By reducing free waste, use it as a secondary material and benefit from it. Integrated waste management technology includes successive steps that take into account the environmental, economic and social spheres of life.